The efficient bond among mobile commerce, CRM and E-loyalty to maximise the productivity of companies - Faed, Alireza; Ashouri, A.; Wu, Chen (IEEE, 2010)
Mobile commerce, has become a significant topic in IS research community and it is a key concept for many businesses, However, it has not fulfilled the expectations. This paper tackles the issue of mobile commerce in three different ways. First, it emphasizes the relative importance of customer relationship management and its relationship with mobile commerce. Second, it illustrates the ways to enhance E-loyalty of the clients within small and medium enterprises. Ultimately, the positive relationship among these, three concepts will be clarified. M-Commerce constitutes an important future market worldwide.This paper argues that businesses should strengthen and enhance loyalty as well as e-loyalty and M-Commerce activities, in order to better acquire the customers toward wireless marketing and customer relationship channels. Moreover to get the most euphoria businesses must create value for consumers in a way that is different from what they get used to prior to the latest version of services from the businesses. This paper, introduces a new area of doing business with the assistance of CRM and some evaluators to grasp loyalty under the context of mobile commerce. In addition, businesses should consider consumer's willingness to use successful features of M-Commerce. While performing the project, we expect to achieve productivity and reputation to the organization.